2021
DOI: 10.1136/bmjopen-2020-046596
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with missed hospital appointments: a retrospective review of multiple clinics at Royal Hospital, Sultanate of Oman

Abstract: ObjectivesMissed hospital appointments pose a major challenge for healthcare systems. There is a lack of information about drivers of missed hospital appointments in non-Western countries and extent of variability between different types of clinics. The aim was to evaluate the rate and predictors of missed hospital appointments and variability in drivers between multiple outpatient clinics.SettingOutpatient clinics in the Royal hospital (tertiary referral hospital in Oman) between 2014 and 2018.ParticipantsAll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The incidence of missed appointments was about two-fold for those patients who covered their medical expenses out of their pocket as compared to those who were waived. This finding was supported by a previous study conducted in Oman [ 33 ]. This may be due to that patients may have no health coverage to pay for their treatment or they have limited coverage that does not cover every health service.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of missed appointments was about two-fold for those patients who covered their medical expenses out of their pocket as compared to those who were waived. This finding was supported by a previous study conducted in Oman [ 33 ]. This may be due to that patients may have no health coverage to pay for their treatment or they have limited coverage that does not cover every health service.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, in the Omani context, a study conducted at the Royal Hospital (tertiary care/specialized care) reported that age, sex, patient’s residence distance from the hospital, waiting time and day, and season were important predictors for no-show. 30 …”
Section: Discussionmentioning
confidence: 99%
“…These observations were further divided into one dataset including appointments scheduled within the Paediatric clinic only ( N = 79,444), another dataset including Obstetrics and Gynaecology appointment only ( N = 51,850) and an overall dataset including scheduled appointments from all remaining outpatient clinics ( N = 177,239). Our previous work observed large variability in the rate of missed appointments by clinic [ 22 ]. Therefore, the top five clinics with highest number of scheduled appointments during the study period and higher rate of missed appointments compared to other clinics were identified and five subsets of data created, including: Diabetes and Endocrine clinic ( N = 42,238), Surgery clinic ( N = 22,781), Oncology clinic ( N = 20,850), Urology clinic ( N = 11,620), and Gastroenterology clinic ( N = 7,946).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work by the research team found that between 2014–2019 the overall rate of missed appointment at The Royal Hospital was 22.3%, ranging from 14% to 30.3% by clinic. The study found that age, sex, service cost, waiting time, appointment day and the distance a patient lived from the hospital were important predictors for missed appointment [ 22 ]. To our knowledge, no such study has been conducted to investigate the impact of COVID-19 on the rate of missed hospital outpatient appointment in Oman.…”
Section: Introductionmentioning
confidence: 99%